Difference in the action spectra for UVR8 monomerisation and HY5 transcript accumulation in Arabidopsis. Issue 8 (11th July 2018) - Díaz-Ramos, L. Aranzazú; O'Hara, Andrew; Kanagarajan, Selvaraju; Farkas, Daniel; Strid, Åke; Jenkins, Gareth I.
Abstract : The action spectrum for monomerisation of the plant UV-B photoreceptor UVR8 peaks at a shorter wavelength than that for HY5 transcript accumulation, mediated by UVR8, in the same tissue. Abstract : The photoreceptor UV RESISTANCE LOCUS 8 (UVR8) activates photomorphogenic responses when plants are exposed to ultraviolet-B (UV-B) light. However, whereas the absorption spectrum of UVR8 peaks at 280 nm, action spectra for several photomorphogenic UV-B responses show maximal photon effectiveness at 290–300 nm. To investigate this apparent discrepancy we measured the effectiveness of UV wavelengths in initiating two responses in Arabidopsis: photoconversion of homodimeric UVR8 into the monomeric form, which is active in signaling, and accumulation of transcripts of the ELONGATED HYPOCOTYL 5 (HY5) transcription factor, which has a key role in UVR8-mediated responses. When purified UVR8 or Arabidopsis leaf extracts were exposed to UV light monomerisation was maximal at approximately 280 nm, which correlates with the UVR8 absorption spectrum. When intact plants were exposed to UV, monomerisation was most strongly initiated at approximately 290 nm, and this shift in maximal effectiveness could be explained by strong absorption or reflectance at 280 nm by leaf tissue. Notably, the action spectrum for accumulation of HY5 transcripts in the same leaf tissue samples used to assay UVR8 dimer/monomer status peaked at approximately 300 nm. Possible reasons for the difference in maximal photon effectiveness of UVR8 monomerisation and HY5 transcript accumulation in leaf tissue are discussed.